The Needs Assessment to Application of E-learning in Teaching and Learning Statistics for Research - Vang, Khammy; Vathanavong, Thongthiane; Chanthahong, Khamxay; Lamphaiphanh, Ketsalinh; Pathoumvanh, Phanthamanath; Sisouphanh, Vetmanysay (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purposes of this research were: 1) to study the state of the problems of teaching and learning for lecturers and undertake a needs assessment for applying E-Learning in teaching and learning statistics for research; and 2) to quality develop of E-Learning. The study sample comprised 56 lecturers and 97 students from Faculty of Education, Souphanouvong University who were selected by simple random sampling. Survey and quantitative method were used as the research methodology. Research Instruments used to collect the data were a questionnaire. Statistics used included percentage, mean (x ), standard deviation (S.D.) and Priority Needs Index Modified (PNIModified). Dependent sample T-test was applied. The research results were as follows: 1) The state of the problems of teaching and learning for lecturers at Souphanouvong University, including the overall average, was medium; meanwhile the needs assessment for applying E- Learning in teaching and learning statistics for research was highest levels. The needs assessment to application of e- learning in teaching and learning statistics for Research by all groups of the sample was an essential requirement for all items, with the overall average of 0.45 (PNIModified = 0.45). The results of using E-Learning were impact to student as the first priority of the PNIModified; secondly were E-Learning system management; third were environment of E-Learning and finally were E-Learning activities management, respectively, and 2) E- Learning had been a good quality on the suitable and consistency with reliability of Cronbach’s Alpha Coeffiecient equal 0.85. The results of this study will be used to application of e-learning in teaching and learning statistics for research